Menikahi Wanita Hamil di Luar Nikah - Tanjung, Dhiauddin (State of Islamic Institute Langsa, 2022)
The problem of pregnant women before the marriage ceremony is taboo for Muslims, because it is rare for men to marry these women, although some cases do. This research purely uses normative legal research methods, because it only discusses legal material contained in statutes and books of fiqh. Based on the results of the analysis, that the Shafi'i and Hanafi schools justify a man marrying a pregnant woman before marriage, while the Maliki and Hanbali schools do not justify it. Article 53 KHI allows pregnant women to marry men who impregnate them. Regarding the status of children born to pregnant women, it is assigned only to the mother, but in the Syafi'i school, the child is assigned to the father, provided that the child is born after 6 months after marriage, whereas if it is under 6 months, it is not permissible. Regarding the correlation between fiqh and KHI regarding the position of pregnant women out of wedlock, it is very much in line especially in the Shafi'i and Hanafi schools where they agree to allow men to marry pregnant women out of wedlock